การนำนโยบายว่าด้วยการส่งเสริมและพัฒนาคุณภาพชีวิตคนพิการไปสู่การปฏิบัติในประเทศไทย - ชุมรัมย์, สุภาพ (Ph.D. in Social Sciences Journal, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษา (1) กระบวนการนำนโยบายสาธารณะว่าด้วยการส่งเสริม และพัฒนาคุณภาพชีวิตคนพิการไปสู่การปฏิบัติโดยเน้นกรณีของกระทรวงการพัฒนาสังคมและความ มั่นคงของมนุษย์ (2) ปัจจัยที่ส่งผลต่อการนำนโยบายส่งเสริมและพัฒนาคุณภาพชีวิตคนพิการไปสู่การปฏิบัติ (3) พัฒนาข้อเสนอแนะเพื่อให้การนำนโยบายว่าด้วยคนพิการสู่การปฏิบัติมีประสิทธิภาพและทั่วถึงมากยิ่งขึ้น โดยการคำนึงถึงสิทธิ และศักดิ์ศรีที่ทัดเทียมกันของคนพิการ โดยมีข้อค้นพบดังนี้ 1.) การนำนโยบายว่า ด้วยคนพิการสู่การปฏิบัติโดยกระทรวงการพัฒนาสังคมและความมั่นคงของมนุษย์ ส่วนใหญ่ต้องดำเนิน ไปตามระบบและระเบียบราชการ แต่การได้รับการสนับสนุนจากฝ่ายการเมืองก็มีความสำคัญ โดยเฉพาะ ด้านการจัดสรรงบประมาณ และการยกระดับสถานภาพของข้าราชการผู้ปฏิบัติงานที่เกี่ยวข้องเพื่อให้มีอำนาจ สั่งการสูงขึ้น 2.) การนำนโยบายสู่การปฏิบัติที่ได้ผลดีขึ้นอยู่กับทักษะในบริหารภายในหน่วยงานของ กระทรวงเอง และความสามารถในการร่วมมือประสานงานกับกระทรวง ทบวง กรม อื่น ๆ ที่เกี่ยวข้อง รวมทั้งกับองค์การภาคเอกชนและตัวคนพิการ 3.) กลไกของระบบราชการให้ความสำคัญกับสายการบังคับ บัญชา และระเบียบ กฎเกณฑ์ละเอียด ผู้รับผิดชอบในด้านการปฏิบัติจึงมักต้องใช้ดุลยพินิจในการหาทาง แก้ไขปัญหาเฉพาะหน้าให้ลุล่วงไปได้ ภายในขอบเขตที่ไม่ละเมิดกฎหมาย 4.) การวิจัยพบว่าสืบเนื่องจาก ข้อจำกัดต่าง ๆ คือ ทรัพยากรบุคลากร งบประมาณ วัสดุอุปกรณ์ และการทำตามกำหนดเวลา ข้าราชการ หรือเจ้าหน้าที่จำเป็นต้องใช้วิธีการแล้วแต่เหมาะสมของตนเองในการแก้ไขปัญหาเฉพาะหน้าและมีการนำ เสนอให้หน่วยเหนือทราบเพื่อหาทางปรับปรุงในโอกาสต่อไป 5.) ความพยายามในการนำนโยบายสู่การ ปฏิบัติ แม้มีอุปสรรคบางประการแต่ภาพรวมคือ ผลลัพธ์อยู่ในด้านบวก ดังตัวอย่างได้แก่ การมีจำนวนผู้ได้ เข้าลงทะเบียนอย่างเป็นทางการว่า “เป็นคนพิการ” ประเภทต่าง ๆ ซึ่งทำให้มีสิทธิในการได้รับบริการต่าง ๆ อันเป็นผลให้มีมาตรฐาน คุณภาพชีวิตที่สูงขึ้น Implementation of the Policy on the Promotion and Development of the Quality of Life of the Disabled in Thailand The objective of this research is to study 1) the implementation process of the public policy to promote and develop the quality of life of the disabled in Thailand as carried out by the Ministry of Social Development and Human Security 2) various factors affecting the implementation process and 3) to propose suggestions and measures in order to achieve the goal. The findings are as follow 1.)The implementation process of the public policy concerning disabled persons (or persons with disabilities) has to follow specific bureaucratic procedures of the Royal Thai Government including those specifically of the Ministry of Social Development and Human Security. It has been found, however, that concrete support from the relevant “political” circle is of some importance, e.g. as regards amount of budget allocation and through the upgrading of certain personnel, particularly those involved directly in the implementation process, since higher rank means higher authority to get things done for the disabled 2.) The success in implementing the policy depends on the administrative skills as well as attentive dedication of various units of the official bureaucracy and those or groups of the private sector, particularly in various organizations of the disabled 3.) Bureaucratic mechanism puts much emphasis on hierarchical line of control and detailed regulations To follow strictly such rigid line and rules would naturally impede the policy implementation in the interest of the disabled. Thus certain conscientions officials to discreetly resort to alternative ways which work but to be sure, does not strictly follow the letters of officially prescribed procedures, albeit not glaringly illegal 4.)The implementation process is more than simplistically following written bureaucratic procedures. It has been found that due to limitations of resources, e.g. “Man, Money, and Material” the Management i.e. implementing officials, “street-level bureaucrats”, to use Pressman and Wildavsky’s key phrase, have at times to resort to their own particular way of adapting to the circumstances in order to come up with certain measures of success and report practical problems to the higher authorities for future remedial measures and 5.) Despite a variety of obstacles in the implementation efforts the outcome has been on the plus side, e.g. as regards higher percentages of those who officially registered as “disabled” or “persons with disabilities” which legally entitle them to be beneficiaries of the policy of the Royal Thai Government in allotting opportunities, things and services in fulfillment of the quality of life of those with different categories of disabilities, in urban or rural areas, male or female, young or elderly in significant number to be eligible for proper service toward their better standard of living.